Metalloproteinase-2 in failed back surgery syndrome caused by epidural fibrosis: can it play a role in persistent pain? - Bielewicz, Joanna; Daniluk, Beata; Kamieniak, Piotr (Frontiers in Human Neuroscience, 2023)
Failed Back Surgery Syndrome (FBSS) occurs in 10-40% of patients treated surgically due to disk herniation (DH). There are several factors which can predispose to FBSS, but the exact patomechanism is not elucidated. The aim of this study was to investigate Metalloproteinase-2 (MMP-2) and Tissue Inhibitor of Metalloproteinase-2 (TIMP-2) activities in the homogeneous group of FBSS patients with epidural fibrosis in comparison to its activity in patients with surgically treated DH. Methods: DH, FBSS and control (CG) groups consisted of 30 subjects. The patients were assessed clinically by the Numerical Rating Scale (NRS), McGill Pain Questionnaire (SF -MPQ), Oswestry Disability Index (ODI) and Beck Depression Inventory (BDI). Serum concentrations of MMP-2 and TIMP-2 were measured, by the immunoenzymatic method.Results:There was a significantly higher MMP-2 expression (medians: 4797.49 vs 2656.65; p<0.0001) and TIMP-2 concentration (medians: 166.40 vs 109.60; p<0.0001) in the DH compared to the CG. Also significantly higher MMP-2 expression (4219.95 vs 2656.65; p<0.0001) and TIMP-2 concentration (medians: 150.17 vs 109.60; p=0.0003) were found in the FBSS compared to the CG. Activity of MMP-2 , measured as MMP-2/TIMP-2 was did not significantly change between the DH, FBSS and CG. MMP2 expression (p<0.0001) and TIMP-2 concentration (p<0.0001) were significantly higher in the DH than FBSS.Results indicate the contribution of MMP-2 and TIMP-2 in DH and FBSS. Unchanged activity of MMP-2 can indicate an insufficiency of MMP-2 repair system, in both diseases.Lower MMP-2 expression and TIMP-2concentration in the FBSS group can reflect the chronicity of process.